Where have we got to on adaptive learning, thinking and working politically, doing development differently etc? Getting beyond the People’s Front of Judea - Algoso, Dave; Hudson, Alan (From Poverty to Power, 2016)
Dave Algoso and Alan Hudson at Global Integrity compare and contrast 9 different initiatives that are all heading in roughly the right direction in aid reform
Keywords: IMPORTANT

Thinking and Working politically to support developmental leadership and coalitions: The Pacific Leadership Program - Denney, Lisa; McLaren, Rebecca (DLP Program, 2016)

Everyday Political Analysis - Hudson, David; Marquette, Heather; Waldock, Sam (Developmental Leadership Program, 2016)
This short note introduces a stripped-back political analysis framework designed to help frontline development practitioners make quick but politically-informed decisions. It aims to complement more in-depth political analysis by helping programming staff to develop the 'craft' of political thinking in a way that fits their everyday working practices. Everyday Political Analysis involves two steps: Understanding interests: What makes people tick? Understanding change: What space and capacity do people have to effect change? For each step five questions, accompanied by prompts, aim to help staff to conduct quick political analysis. The EPA framework can be used at any stage of the aid management cycle, and can help users to respond rapidly to unexpected change. We are keen to hear back from people on their experience of using EPA to help us adapt the framework. Was it useful (or not)? Do people tend to use just one or both steps? Are there missing statements or prompts that would improve the analysis? Please email us at info [at] dlprog.org.